Descriptive Analysis of Rheumatic Heart Disease Related Complications in Pediatric Patients at Tertiary Hospital, Addis Ababa, Ethiopia - Desta TT; Gezachew A; Eshetu K (Dove Medical Press, 2023)
Temesgen Tsega Desta,1 Alem Gezachew,1 Konjit Eshetu2 1Department of Pediatrics and Child Health, Saint Paul Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Department of Pediatrics and Child Health, Haramaya University College of Health and Medical Sciences, Harar, EthiopiaCorrespondence: Temesgen Tsega Desta, Email yafettemu@gmail.comIntroduction: Rheumatic heart disease continues to be a public health problem worldwide. In developing countries such as Ethiopia where rheumatic heart disease is endemic, most of the patients present with complaints related to complications including heart failure, arrhythmias, pulmonary hypertension, stroke, systemic embolic events and infective endocarditis.Objective: To identify the types and magnitude of complications in pediatric patients with rheumatic heart disease.Methodology: Hospital-based cross-sectional study was conducted at Saint Paul Hospital Millennium Medical College, pediatric and child health department. All pediatric cardiac patients with rheumatic heart disease seen from January 1, 2018 to December 30, 2021 were included in the study.Conclusion: The majority of patients presented to our health facility with complications which implies the need for action at the community level to detect the disease at early stage.Recommendations: We recommend a similar large-scale study to be conducted at the national level and introduce a national RHD registry to better understand the magnitude of the problem, based on which necessary action will be undertaken. There is also a need to assess the proper implementation of screening and preventive RHD programmes.Keywords: rheumatic heart disease, heart failure, pulmonary hypertension and malnutrition